Dosage reduction and discontinuation of biological disease-modifying antirheumatic drugs in patients with rheumatoid arthritis, psoriatic arthritis and axial spondyloarthritis: protocol for a pragmatic, randomised controlled trial (the BIOlogical Dose OPTimisation (BIODOPT) trial). Issue 7 (9th July 2019) - Uhrenholt, Line; Schlemmer, Annette; Hauge, Ellen-Margrethe; Christensen, Robin; Dreyer, Lene; Suarez-Almazor, Maria E; Kristensen, Salome
Abstract : Introduction: The The BIOlogical Dose OPTimisation (BIODOPT) trial is a pragmatic, multicentre, randomised controlled, open-label, parallel-group, equivalence study designed to evaluate tapering of biological disease-modifying antirheumatic drugs (bDMARDs) in patients with rheumatoid arthritis (RA), psoriatic arthritis (PsA) and axial spondyloarthritis (axSpA) in sustained clinical remission or low disease activity (LDA). Traditionally, these patients maintain standard dosage of bDMARD lifelong; however, recent studies indicate that a significant proportion of patients in sustained remission or LDA can taper their bDMARD and maintain stable disease activity. Thus, this trial aims to evaluate whether a disease activity-guided tapering strategy for bDMARDs will enable a significant dosage reduction while maintaining disease activity compared with usual care. From the individual patient's standpoint as well as from a societal perspective, it would be advantageous if bDMARDs could be reduced or even discontinued while maintaining disease activity. Methods and analysis: A total of 180 patients with RA, PsA or axSpA treated with bDMARDs and in clinical remission/LDA during the past 12 months will be enrolled from four centres in Denmark. Patients will be randomised in a ratio of 2:1 to either disease activity-guided tapering of bDMARDs (intervention group) or continuation of bDMARDs as usual care (control group). The primary objective is the difference between the two groups in the proportion of patients who have reduced their inclusion dosage of bDMARDs to 50% or less while maintaining stable disease activity at 18 months follow-up. Ethics and dissemination: The study is approved by the ethics committee of Northern Jutland, Denmark (N-20170073) and by the Danish Medicine Agency. Patient research partner KHH contributed to refinement of the protocol and approved the final manuscript. Results will be disseminated through publication in international peer-reviewed journals. Trial registration number: 2017-001970-41; Pre-results.